Workplace Discrimination, Role Conflict, and Mental Health: Understanding Women’s Psychological Experiences at Work - Dhabhai, Ishika (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The modern workplace, while advancing in gender inclusivity, continues to pose significant psychological challenges for women. This study explores the intersection of workplace discrimination, role conflict, and mental health to understand the complex psychological experiences of women at work. Drawing upon empirical literature, psychological theories, and qualitative data, the research investigates how overt and subtle forms of gender-based discrimination—including unequal pay, biased promotion practices, and microaggressions—impact women’s self-esteem and job satisfaction. The study also delves into role conflict, particularly the tension between professional responsibilities and domestic expectations, which often exacerbates stress and leads to burnout. The mental health consequences of these challenges are analyzed through indicators such as anxiety, depression, and emotional exhaustion. Using a mixed-methods approach combining surveys and in-depth interviews, this research aims to highlight systemic patterns, individual coping strategies, and the psychological toll of gendered workplace dynamics. The findings underscore the urgent need for organizational reforms, supportive policies, and mental health interventions that promote gender equity and psychological well-being in professional environments.